2014
DOI: 10.1542/peds.2014-1092
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Vitamin K Refusal and Nonimmunization

Abstract: BACKGROUND: Neonatal Vitamin K prophylaxis is an effective intervention for reducing vitamin K deficiency bleeding. A recently published report of parental refusal of vitamin K prompted an investigation of the prevalence and characteristics of this group, and exploration of whether these same parents were likely to subsequently refuse immunization for their children. METHODS: We conducted a retrospective population-based coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 20 publications
3
65
1
1
Order By: Relevance
“…14 The main reason for this difference between countries is perhaps seen in the more than two-fold increase in oral vitamin K in our cohort. It is, however, reassuring that 97% of parents overall consented for some form of vitamin K prophylaxis.…”
Section: Design and Data Sourcesmentioning
confidence: 74%
See 1 more Smart Citation
“…14 The main reason for this difference between countries is perhaps seen in the more than two-fold increase in oral vitamin K in our cohort. It is, however, reassuring that 97% of parents overall consented for some form of vitamin K prophylaxis.…”
Section: Design and Data Sourcesmentioning
confidence: 74%
“…Further study is needed to confirm this. However, this was seen in the Canadian setting, 14 where those opting for a planned home birth were about five times more likely to decline vitamin K.…”
Section: Design and Data Sourcesmentioning
confidence: 97%
“…16,17 This may be due to women who choose midwifery care having alternative beliefs regarding health care interventions, as evidenced by recent literature showing decreased vaccination rates and neonatal vitamin K prophylaxis among children born to women who sought midwife care. 18,19 This trend might also be due to midwifery's principles of encouraging informed choice for independent decision making. 20,21 Women using midwives in our cohort were older, and less likely to be First Nations, single and in the lowest income quintile than women not using midwives.…”
Section: Discussionmentioning
confidence: 99%
“…In a Canadian cohort, 0.3% of children did not receive vitamin K owing to parental refusal. 2 Incidence of vitamin K refusal in the United States is unknown but likely varies by geography, delivery clinician, and delivery setting.…”
Section: Carrie Phillipi MD Phd Commentsmentioning
confidence: 99%
“…A different study showed increased likelihood of vitamin K refusal among those who chose midwife delivery, suggesting a role for targeted prenatal counseling by trusted providers who care for those most likely to decline it. 2 The second question central to this case is whether clinicians should offer or support oral vitamin K. We know oral vitamin K preparations used in Europe are effective in prevention of classic VKDB, but they are less effective in prevention of late VKDB. 24 In the United States, oral preparations include vitamin K intravenous solution, compounded vitamin K tablets, and a mail-order liquid preparation.…”
Section: Melissa Weddle MD Mph Commentsmentioning
confidence: 99%